Identification of Antimicrobial Compounds in Two Streptomyces sp. Strains Isolated From Beehives - Santos-Beneit, Fernando; Ceniceros, Ana; Nikolaou, Athanasios; Salas, José A.; Gutierrez-Merino, Jorge (Frontiers in Microbiology, 2022)
The World Health Organization warns that the alarming increase in antibiotic resistant bacteria will lead to 27 million deaths annually due to the lack of effective antibiotic therapies. Clearly, there is an urgent need for short-term alternatives that help alleviate these alarming figures. In this respect, the scientific community is exploring neglected ecological niches from which the prototypical antibiotic-producing bacteria Streptomycetes are expected to be present. Recent studies have reported that honeybees and their products carry Streptomyces species that possess strong antibacterial activity. In this study, we have investigated the antibiotic profile of two Streptomycetes strains that were isolated from beehives. One of the isolates is the strain Streptomyces albus AN1, which derives from pollen, and shows potent antimicrobial activity against Candida albicans. The other isolate is the strain Streptomyces griseoaurantiacus AD2, which was isolated from honey, and displays a broad range of antimicrobial activity against different Gram-positive bacteria, including pathogens such as Staphylococcus aureus and Enterococus faecalis. Cultures of S. griseoaurantiacus AD2 have the capacity to produce the antibacterial compounds undecylprodigiosin and manumycin, while those of S. albus AN1 accumulate antifungal compounds such as candicidins and antimycins. Furthermore, genome and dereplication analyses suggest that the number of putative bioactive metabolites produced by AD2 and AN1 is considerably high, including compounds with anti-microbial and anti-cancer properties. Our results postulate that beehives are a promising source for the discovery of novel bioactive compounds that might be of interest to the agri-food sector and healthcare pharmaceuticals.